Barriers for implementation of cosmetovigilance in Peru: Structural Equation Modeling Using Partial Least Square - Del-Aguila-Arcentales, Shyla; Alvarez-Risco, Aldo; Diaz-Risco, Santiago (Ars Pharmaceutica (Internet), 2018)
Aim: This paper examines the barriers in Peruvian community pharmacies for cosmetovigilance practice. Methods: It was obtained information from the pharmacists of 81 community pharmacies in 2 districts in Lima, Peru. For reliability´s evaluation, it was used SPSS software V.24. The validity of construct, discriminant validity and, internal consistency by the composite reliability was analyzed with structural equation modelling using partial least square using SmartPLS 3 software. Results: 81 questionnaires self-administered anonymous were completed (response rate = 51.9%). Average of years of working in community pharmacies was more than 6.36 years (SD: 4.63). More than 70% of the participating pharmacists chose the «strongly agree» and «agree» alternative for items about barriers that included: Lack of time, National health system structure in general and My interest to report adverse reaction by cosmetics. About daily activities, more than 70% of the participants chose the «strongly agree» and «agree» alternative for items that included «Rarely I explain to users about adverse reaction with cosmetics use» and «Rarely I have material to inform to users about adverse reaction with cosmetics use». The composite reliability for each latent variable was Resources: 0,766; Interest: 0862; Regulation: 0.815 and Cosmetovigilance Practice: 0.909. Conclusion: The need of the implementation of cosmetovigilance practice is an issue of public health to take responsibility for care customers against cosmetic damage.